Revision of the total nitrogen and phosphorus content in a cattle manure-based organic fertiliser in North-West Russia - Shalavina, Ekaterina; Briukhanov, Aleksandr; Luostarinen, Sari; Trifanov, Alexey; Kozlova, Natalia; Vasilev, Eduard; Subbotin, Igor (Scientific Agricultural Society of Finland, 2021)
This study aimed to verify the applicability of a mass balance method for estimating nitrogen (N) and phosphorus (P) content in the solid organic fertiliser produced from cattle manure in North-West Russia. The study compared the relevant established norms in Russia, the data calculated by the mass balance method, and the average experimental data on N and P content in cattle manure (ex-housing) and the organic fertilizer ready to use from the selected cattle-breeding complex with 1250 heads and a manure output of 70 t day-1. Three animal categories were considered. The difference between the calculated and experimental data was 10% maximum but the experimental data and the established norms differed by above 15%. This proves the demand to revise the norms in the Russian regulatory documents to improve the accuracy of fertiliser application rates and the estimation of agricultural land required. Even an increase of 10% in the nutrient content of the organic fertiliser results in an increase in the required agricultural land from 451 to 526 ha for spreading the organic fertiliser from the 1250 heads of cattle at the selected farm.
Keywords: lanta; kotieläintalous; eläinsuojat; lantalat; ravinteet; ravinnekierto